Optimization of Free Nutritious Meal Supply Chain Program in Support of Indonesia's Non-Military Defense Force - Sukmasari, Dyah; Aritonang, Sovian; Sudiarso, Aries; Pujianto, Koko (Jurnal Ilmiah Global Education, 2025)
Purpose: This study aims to analyze the optimization of the supply chain in the Free Nutritious Meal (MBG) Program to support Indonesia’s non-military defense force. The research focuses on evaluating supply chain challenges, assessing the impact of efficient logistics and stakeholder collaboration, and proposing strategic improvements to enhance food security and national resilience. Design/methodology/approach: This research employs a qualitative descriptive approach through a literature review of academic publications, government policies, and international reports on food supply chains and national security. The study examines key supply chain components, inefficiencies, and potential solutions to strengthen the sustainability of the MBG Program. Findings: The findings indicate that the effectiveness of the MBG Program depends on an efficient supply chain encompassing production, distribution, and consumption. Key challenges include logistical constraints, production sustainability, and multi-stakeholder coordination. Implementing strategic measures such as digital supply chain management, infrastructure investment, and local food diversification can enhance program efficiency and contribute to Indonesia’s non-military defense strategy. Originality/value: This research contributes to the fields of food security and national resilience by providing a strategic framework for optimizing the MBG Program’s supply chain. It offers practical recommendations for policymakers, supply chain managers, and stakeholders to establish a more resilient and adaptive food security system.